Ungku Omar Ungku Ahmad - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Ungku Omar Ungku Ahmad (1931-1969), was an influential Malaysian physician and clinical chemist. Born on 18 January in Johor Bahru, he attended Malay schools in Kluang, Segamat, Pontian and Tangkak in Johor between 1938-1944, and the Johor Religious School until he passed standard 6.